Influence of hydrodynamic coefficients in the response behavior of triangular TLPs in regular waves - Chandrasekaran S.; Jain A.K.; Chandak N.R. (My University, 2025)
Triangular configuration tension leg platforms (TLPs) are used for deep-water oil/gas exploration. The mechanics of TLP is highly nonlinear due to larger structural displacements and fluid motion-structure interaction. Triangular TLP has major consideration for deep-water application also due to its relative insensitivity with increasing water depth, excellent station keeping characteristics, etc. which makes this as a most cost effective and practical production system for deep waters. This study focuses on the influence of hydrodynamic drag coefficient (Cd) and hydrodynamic inertia coefficient (Cm) on the nonlinear response behavior of triangular TLP models under regular waves. Two typical triangular TLP models vis-à-vis TLP1 and TLP2 are taken for the study at 600 and 1200 m water depths, respectively. Hydrodynamic forces on these TLPs are evaluated using modified Morison equation under regular waves. Diffraction effects are neglected. Various nonlinearities arising due to relative velocity term in drag force, change in tether tension due to TLP movement, and set down effect are being considered in the analysis. The dynamic equation of motion has been solved in time-domain by employing Newmark's β numerical integration technique. Based on the numerical study conducted, it is seen that the response evaluated using varying hydrodynamic coefficients through the water depth is significantly lesser in comparison to the response with constant coefficients in all activated degrees-of-freedom. However, sway, roll, and yaw degrees-of-freedom are not present due to the unidirectional wave loading considered for the study. The influence of hydrodynamic coefficients in wave period of 15 s is more in comparison with that of 10 s, and is nonlinear. The hydrodynamic coefficients also influence the plan dimension of TLP and its site location (geometry). Therefore, it may become essential to estimate the range of Cd-Cm values to vary through the water depth, based on Reynolds number (Re) or Keulegan-Carpenter number (Kc) even before the preliminary design of the TLP geometry. © 2004 Elsevier Ltd. All rights reserved.